Addressing Email Loss with SureMail: Measurement, Design, and Evaluation - Agarwal, Sharad; Padmanabhan, Venkat; Joseph, Dilip (Usenix Annual Technical Conference, 2007)
We consider the problem of silent email loss in the Internet, where neither the sender nor the intended recipient is notified of the loss. Our detailed measurement study over several months shows a silent email loss rate of 0.71% to 1.02%. The silent loss of an important email can impose a high cost on users. We further show that spam filtering can be the significant cause of silent email loss, but not the sole cause. SureMail augments the existing SMTP-based email infrastructure with a notification system to make intended recipients aware of email they are missing. A notification is a short, fixed-format fingerprint of an email, constructed so as to preserve sender and recipient privacy, and prevent spoofing by spammers. SureMail is designed to be usable immediately by users without requiring the cooperation of their email providers, so it leaves the existing email infrastructure (including anti-spam infrastructure) untouched and does not require a PKI for email users. It places minimal demands on users, by automating the tasks of generating, retrieving, and verifying notifications. It alerts users only when there is actual email loss. Our prototype implementation demonstrates the effectiveness of SureMail in notifying recipients upon email loss.